Environmental histories of the First World War - The Global Environmental History of World War I in Perspective; Tucker, Richard P. 1938- Herausgeber; Keller, Tait ca. 20./21. Jh. Herausgeber; McNeill, John Robert, 1954- 1954- Herausgeber; Schmid, Martin, 1974- 1974- Herausgeber (Cambridge University Press, 2018)
This anthology surveys the ecological impacts of the First World War. Editors Richard P. Tucker, Tait Keller, J. R. McNeill, and Martin Schmidt bring together a list of experienced authors who explore the global interactions of states, armies, civilians, and the environment during the war. They show how the First World War ushered in enormous environmental changes, including the devastation of rural and urban environments, the consumption of strategic natural resources such as metals and petroleum, the impact of war on urban industry, and the disruption of agricultural landscapes leading to widespread famine. Taking a global perspective, Environmental Histories of the First World War presents the ecological consequences of the vast destructive power of the new weaponry and the close collaboration between militaries and civilian governments taking place during this time, showing how this war set trends for the rest of the century